Successful surgical management of a cerebellar subdural empyema in a domestic cat - Hall, Ian; Hamon, Martin; Bruwier, Aurelie; González Blancas, Sara Michell; Picavet, Pierre P. (Frontiers in Veterinary Science, 2025)
This case report describes the successful diagnosis and surgical management of a cerebellar subdural empyema in a 14-year-old Domestic Shorthair cat. The patient presented with a left-sided head tilt and right-sided hemiparesis. Magnetic resonance imaging (MRI) revealed a right-sided extra-axial cavitated lesion in the cerebellum, and mild right-sided otitis media without evidence of otitis interna. Surgical decompression was performed, guided by the use of a 3D-printed model, and purulent material was evacuated. Bacterial culture identified Peptostreptococcus canis, Filifactor villosus, and a Gram-negative rod population; all were suspectible to amoxicillin-clavulanic acid. Cerebellar subdural lesion histopathologic analysis confirmed a pyogranulamatous to lymphoplasmocytic inflammatory process. The patient showed rapid postoperative neurological improvement and was discharged with targeted antimicrobial therapy. Follow-up MRI at 2 months revealed resolution of the cerebellar lesion but progression of right-sided otitis media without evidence of otitis interna. A ventral bulla osteotomy was subsequently performed, and tympanic mucosa biopsy confirmed chronic inflammation with cholesterol granuloma formation. To our knowledge, this is the first report of successful surgical treatment of a cerebellar subdural empyema in a feline patient.